Association Between Types of Chronic Disease and Receiving Workplace Accommodations: A Cross-Sectional Study of Japanese Workers. Issue 2 (February 2023) - Harada, Arisa; Tateishi, Seiichiro; Ishimaru, Tomohiro; Nagata, Masako; Eguchi, Hisashi; Tsuji, Mayumi; Ikegami, Kazunori; Matsugaki, Ryutaro; Fujino, Yoshihisa
Abstract : Chronic diseases with frequent workplace accommodations may be encouraged by the law and policy. Conversely, chronic diseases that are perceived as personal problems or those that are difficult to diagnose objectively may be less likely to receive workplace accommodations and need additional support. Abstract : Objective: This study aimed to evaluate the association between the type of chronic disease and receiving workplace accommodations. Methods: This online cross-sectional study analyzed a self-reported questionnaire administered in Japan. A total of 6775 full-time workers who reported needing work accommodations were included. Results: Workplace accommodations were more likely to be provided for workers with cancer, mental illness, and benign gynecological disorders than for workers with no disease under treatment. In contrast, workplace accommodations were less likely for workers with low back pain and skin diseases. Conclusions: Receiving workplace accommodations depends on the type of chronic disease. Chronic diseases for which workers frequently receive workplace accommodations may be those for which support is encouraged by law. It is necessary to support workers with chronic diseases that do not receive adequate workplace accommodations.